Neonatal CSF Creatine Kinase and CP Risk - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Creatine kinase brain isoenzyme (CK-BB) was examined in the cerebrospinal fluid of 150 neonates at the Departments of Pediatrics and Neonatal Medicine and Clinical Chemistry, University Hospital, Ghent, Belgium.